Water quality modeling of Laguna De Bay with emphasis on salinity, dissolved oxygen and biochemical oxygen demand - Chua, Grace Lawas (2006)
Laguna de bay is the largest and most vital body of water in the Philippines. The lake has been usedfor different purposes such as fisheries, power generation, transportation, reservoir for floodwater, water supply for irrigation, recreation, industrial cooling and potential raw water supply for drinking water. Due to population growth, deforestation, land conversion, urbanization and industrialization over the past decades, its water quality has deteriorated steadily. Conflicting uses of this water resource must resolved to ensure the sustainable development of Laguna de Bay.